Acute respiratory distress syndrome in paediatric scrub typhus. (October 2021) - Loganathan, Sathish K; Jaybhaye, Amol; Dash, Nabaneeta; Punnen, Anu; Ghosh, Urmi; Rose, Winsley
Acute respiratory distress syndrome is a life-threatening complication of scrub typhus; we sought to describe its mortality and associated factors, namely eschar, hepatomegaly and severe thrombocytopenia, in a retrospective study in India of 65 children.